Evaluation Of Pharmacologic Inhibitors Of Platelet Function In Baboons - Hanson, S R; Harker, L A (Thrombosis and Haemostasis, 1981)
The ability of aspirin (ASA), dipyridamole (DIP), sulfinpyrazone (SP) and combinations of these agents to prevent arteriovenous cannula thromboembolism In baboons .has been assessed by measuring the destruction of autologous 51Cr-platelets. In 24 studies with untreated baboons (10-12 kg), thrombogenic polyurethane femoral A-V cannulap (Biomer, 50 cm, 4 mm i.d.) consumed 22.5 ± 4.5 × 108 plats/cm2 -day. In animals with identical shunts, the efficacy of various antithrombotic treatment regimens was determined by measuring the percent reduction in platelet consumption (PC) compared to untreated control values. All drugs were given to at least four animals by oral administration twice daily.ASA, 3-100 mg/kg/day, did not significantly reduce PC (p >0.2). SP In doses of 10, 50 and 100 mg/kg/day reduced PC by 7, 48, and 97% respectively. DIP, 1, 2.5, 5, 10 mg/kg/day, reduced PC by 14, 34, 5l,and 99% and was significantly more effective than SP (p <10-5). ASA (10, 15, 20 mg/kg/day) given with DIP (2.5 mg/kg/day) reduced PC by 47, 67, and 94% demonstrating significant and dose dependent potentiation of DIP by ASA. ASA (10 mg/kg) potentiated DIP (2.5 mg/kg/day) less effectively when given only with the first dose of DIP, or when given twice daily but two hours after administration of DIP (p <0.01). In both cases PC was reduced about 67% (vs. 94% for simultaneous administration twice daily). DIP (2.5 mg/kg/day) plus SP (10, 20, 40 mg/kg/day) reduced PC by 50, 51, and 72% in an additive fashion without potentiation. Similarly SP (20 mg/kg/day) given with DIP (2.5 mg/kg/day) plus ASA (10 mg/kg/day) reduced PC by 65% In an additive manner.It is concluded that PC Is more effectively reduced by DIP than either SP or ASA. DIP Is potentiated by ASA but not SP. DIP and ASA should be administered simultaneously in multiple daily doses.